Hospital Admissions for Hyperglycemic Emergencies in Young Adults at an Inner-City Hospital - Wolf, Rachel A (Diabetes Res Clin Pract, 2019)
AIMS: There is limited information characterizing young adults (18-35 years) (YA) with diabetes, especially those admitted for hyperglycemic emergencies. The study aims were to examine associations of patient-level characteristics with hyperglycemic emergency hospitalization and to identify variations based on diabetes type and glycemic control. METHODS: We conducted retrospective analysis of 273 YA admitted to an inner-city hospital with diabetic ketoacidosis (DKA) or hyperosmolar hyperglycemic nonketotic syndrome (HHS). T-tests, Chi-Square tests, and ANOVA identified differences in demographics, diabetes history, clinical indicators, complications/comorbidities, and hospital admission stratified separately by diabetes type (1 vs 2) and admission HbA1c <9% (75mmol/mol), ≥9% to 12% (108mmol/mol), ≥12%). RESULTS: Mean admission HbA1c was 12.4% (112mmol/ml). HbA1c was ≥9.0% for 90.5%. The main DKA/HHS trigger was medication nonadherence (57.9%), with 35.6% presenting with new-onset type 2 diabetes. Only 3.7% utilized outpatient diabetes clinics, 38.8% were re-hospitalized within the year, and 69% lacked insurance. Diabetes complications (44.7%) and psychiatric co-morbidities (35.5%) were common. Significantly more YA with type 1 diabetes had insurance, whereas YA with type 2 diabetes had higher admission HbA1c. YA with HbA1c ≥12% were more likely to be Black and lack insurance. CONCLUSIONS: YA hospitalized for DKA/HHS in an inner-city hospital tended to have severely uncontrolled diabetes. Many already had comorbidities and diabetes complications, high use of acute care services and low use of diabetes specialty services. YA characteristics varied by diabetes type and HbA1c. Overall, a substantial percentage lacked insurance, potentially impacting healthcare utilization patterns and medication adherence, and leading to DKA/HHS admissions.